PENGARUH SUMBER SEJARAH DAN KEMAMPUAN BERPIKIR HISTORIS TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH DI SMA NEGERI 6 SIGI - Daryanti, Fitri (Katalogis, 2017)
This article aims to analyze the: 1) the effect of utilization of primary historical sources and utilization of secondary historical sources against the results of student learning on subjects of history in class X SMA Negeri 6 Sigi; 2) the effect of the ability of thinking historically high and low historical thinking ability against the results of student learning on subjects of history in class X SMA Negeri 6 Sigi. Experimental research using factorial design research. The population in this research is the grade X SMA Negeri 6 Sigi, namely: class X B as class experiments and class X A class as the control. Class assignment technique using random sampling. The independent variable in this study is a model of historical sources and historical thinking and the dependent variable is the score results study subjects history. Data collection is done with the test results of the study. Validation and reabilitas are calculated using excel. Test requirements using the help of SPSS 19 that includes a test of normality by wearing a Kolmogorov Smirnov test of its homogeneity and wear the Levene Test. Hypothesis testing using anova on ranks the significance of 0.05. The results of the research and testing of the first hypothesis shows F calculate 277.920 with probability of 0.000. Therefore the probability of 0.05, then < H0 is rejected. Thus summed up:1) affect the utilization of primary historical sources and utilization of secondary historical sources against the results of student learning on subjects of history in class X SMA Negeri 6 Sigi;2) there is the effect of historical thinking ability of high and low historical thinking ability against the results of student learning on subjects of history in class X SMA Negeri 6 Sigi; 3) there is the effect of the interaction between the learning that utilizes primary source and secondary source that utilizes learning towards the learning outcomes of students in the subjects of history in class X SMA Negeri 6 Sigi.